(untitled) (CIPEEX, 2025)
Introduction: Rare skin diseases, such as epidermolysis bullosa, Stevens-Johnson syndrome, phlebitis, psoriasis, and systemic lupus erythematosus, present high clinical complexity and significant physical and psychological impact¹. These conditions share common challenges, including recurrent wounds, chronic pain, susceptibility to infections, and the demand for continuous, multidisciplinary care. Recent advances in biological therapies, dermal substitutes, and tissue engineering have expanded therapeutic possibilities and improved patients’ quality of life². Objective: To review current evidence on rare skin diseases associated with wound care, highlighting their clinical features, complications, and modern therapeutic approaches. Methods: This is a narrative literature review based on scientific articles from the database PubMed, also were used official government documents regarding rare skin diseases. Publications from international databases, such as PubMed, as well as governmental health agencies, were analyzed, prioritizing recent studies on pathophysiology, diagnosis, and treatment strategies. Results: Epidermolysis bullosa is characterized by extreme cutaneous fragility, leading to recurrent blistering, infections, and chronic pain. Recent studies demonstrated promising outcomes with low-dose calcipotriol ointment³ and gene therapy strategies such as intravenous gentamicin for type VII collagen expression⁴. Stevens-Johnson syndrome, a severe and often drug-induced reaction, presents with acute necrosis of the skin and mucous membranes and requires immediate withdrawal of the triggering agent along with intensive supportive care; novel approaches such as mucous membrane grafting with fibrin glue or sutures have shown improved recovery⁵. Phlebitis, although not strictly rare, frequently complicates intravenous catheter use and can progress to thrombosis or infection. Studies identified risk factors⁶ and confirmed the effectiveness of topical therapies⁷. Psoriasis, a chronic inflammatory dermatosis, has benefited from biological agents, with meta-analyses showing superior outcomes of adalimumab compared with methotrexate⁸ and evidence that psychological interventions can improve wound healing in surgical patients⁹. Finally, systemic lupus erythematosus, a multifaceted autoimmune condition, continues to require corticosteroids and immunosuppressants, but recent findings revealed the potential role of indole-3-carbinol in regulating wound-healing genes¹⁰, while monoclonal antibody therapies such as belimumab have demonstrated efficacy in refractory cases¹¹. Conclusion: The management of rare skin diseases requires updated knowledge, multidisciplinary collaboration, and access to innovative therapies. Despite remarkable advances, challenges remain regarding treatment availability, standardization of care, and adequate medical training. Continuous investment in research and education is fundamental to optimize patient outcomes.